PENGARUH BRAND AMBASSADOR, SALES PROMOTION DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE - Oky Pujianto; Andhatu Achsa; Ivo Novitaningtyas (Airlangga Journal of Innovation Management, 2023)
The increasing number of e-commerce in Indonesia makes competition among e-commerce increasingly tight. Shopee is an e-commerce in Indonesia which succeeded in occupying the first position as the e-commece platform of choice for the Indonesian people in 2022, besides that in the first quarter of 2022 Shopee also experienced an increase in opinion reaching 64.4 percent and shopee experienced an increase in gross transaction value of 38.7 percent. Purchasing decisions made in this E-commerce are an important factor in the achievement of the increase achieved by shopee e-commerce, of course before consumers make transactions consumers will consider aspects of brand ambassadors, sales promotion, and also brand awareness. This research is quantitative research. The data collection used in this study was through direct surveys to 150 research respondents using the Classical Assumption Test and Multiple Linear Regression Test with the help of the SPSS 24 data processing tool. The results showed that the variables of brand ambassador, sales promotion and brand awareness had a significant and significant effect on purchasing decisions in Shopee e-commerce. The results of the f test show the results that the brand ambassador, sales promotion, and brand awareness variables simultaneously have a positive and significant effect on the purchasing decision variable in Shopee e-commerce.